Ocean Observations in Support of Studies and Forecasts of Tropical and Extratropical Cyclones - Domingues, Ricardo; Kuwano-Yoshida, Akira; Chardon-Maldonado, Patricia; Todd, Robert E.; Halliwell, George; Kim, Hyun-Sook; Lin, I.-I.; Sato, Katsufumi; Narazaki, Tomoko; Shay, Lynn K.; Miles, Travis; Glenn, Scott; et al. (Frontiers in Marine Science, 2019)
Over the past decade, measurements from the climate-oriented ocean observing system have been key to advancing the understanding of extreme weather events that originate and intensify over the ocean, such as tropical cyclones (TCs) and extratropical bomb cyclones (ECs). In order to foster further advancements to predict and better understand these extreme weather events, a need for a dedicated observing system component specifically to support studies and forecasts of TCs and ECs has been identified, but such a system has not yet been implemented. New technologies, pilot networks, targeted deployments of instruments, and state-of-the art coupled numerical forecast models have enabled advances in research and forecast capabilities and illustrate a potential framework for future development. Here, applications and key results made possible by the different ocean observing efforts in support of studies and forecasts of TCs and ECs as well as recent advances in observing technologies and strategies are reviewed. Then a vision and specific recommendations for the next decade are discussed.